Analisis Populasi Kalawet (Hylobates agilis albibarbis) di Taman Nasional Sebangau, Kalimantan Tengah - Suyanti .; Sri Supraptini Mansjoer; Ani Mardiastuti (Pusat Studi Satwa Primata LPPM-IPB, 2009)
Kalawet (Hylobates agilis albibarbis) is one of Hylobates species that naturally living in Kalimantan and can be found in the Natural Peat Swamp Forest Laboratory (LAHG) CIMTROP of Palangkaraya University, Sebangau National Park, Central Kalimantan. This research was aimed to assess the population of kalawet. It was carried out in July up to October 2005. The line transect sampling method was used to survey population. The results of population survey of 6 km2 of mixed swamp forest found 15 groups of kalawet, which consisted of 2-4 individuals/group. The population density was 7.67 individuals/km2 with group density of 2.5 groups/km2 and average group size of 3 individuals/group.Keywords: population, kalawet, Sebangau National Park